การศึกษาและสร้างกังหันลมต้นแบบที่มีประสิทธิภาพและเก็บข้อมูลทางด้านสมรรถนะ และโครงสร้างของกังหันลม : รายงานฉบับสมบูรณ์ - สมศักดิ์ ไชยะภินันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 1995)
This report covers theory and the development of computer programs for predicting the shape of optimized turbine blade, performance and stress of a three bladed horizontal axis wind turbine. Study, construct an optimized turbine and testings for turbines performance and stress are presented along with the comparison of presictions from computer program with test data. Two wind turbines were constructed and tested with a wind tunnel and a moving truck. Testing for performance and for stress were conducted with different instrumentation and different occasions. Test results are compared to the predictions form computer program for verification. Performance predictions in term of power coefficient corrected with Reynolds number effect from computer program show good agreement with test results obtained from the wind tunnel. The accuracy of the predictions is greatly relied on the available of aerodynamic data of the turbine blade cross section over the whole operating range including in the stall region. Stress predictions for the turbines did not show good agreement with test results especially bending stress from aerodynamic load. The explanation of the difference can be traced to the doubt in test results validity due to problems of instrumentation and wind tunnel. It was found that the performance of the optimized wind turbine will be high only when opearting under certian Reynolds number which is high enough to avoid drag penalty (i.e. increasing chord and blade lenght and wind velocity).